Fundamental and macroeconomic analysis of stock prices in the consumer non-cyclicals sector listed on the Indonesia Sharia Stock Index - Hanani, Muhammad Muizul; Nafis, Abdul Wadud; Is’adi, Munir (Journal of Islamic Economics Lariba, 2024)
IntroductionInvestors looking for investment choices that comply with sharia law find the Indonesian capital market, namely the Islamic Sharia Stock Index, to be of utmost importance. Understanding the elements that influence stock price movements in the consumer non-cyclicals sector from 2017 to 2022 is necessary.ObjectivesThe objective of this study is to examine the influence of Return on Assets (ROA), Earnings Per Share (EPS), Debt to Equity Ratio (DER), inflation, and exchange rates on stock prices in the consumer non-cyclicals sector that is listed on the Indonesia Sharia Stock Index (ISSI). The objective is to ascertain the impact of these variables, both individually and together, on stock prices.MethodThe study employed a quantitative descriptive methodology, gathering data from 2017 to 2022 via official corporate websites. The analysis utilized panel data regression and conducted classical assumption testing using EViews.ResultsThe results indicate that Return on Assets (ROA), Earnings per Share (EPS), inflation, and exchange rates all have a considerable influence on stock prices. However, DER does not have a substantial individual impact. The F-test demonstrates a statistically significant combined impact of independent variables on stock prices.ImplicationsThe results underscore the significance of fundamental financial performance and macroeconomic factors for investors and governments when making investment decisions. Gaining proficiency in financial management and comprehending the macroeconomic effects can provide more effective guidance for investment plans in the consumer non-cyclicals sector.Originality/NoveltyThis study offers novel insights into the dynamics of stock price changes in the context of Sharia-compliant investments, specifically in the consumer non-cyclicals sector. It contributes to the broader understanding of the factors that influence stock prices in Islamic capital markets.